The Effect of Reactant Compositions on The Microstructure of Ceramic Materials Formed by Combustion Synthesis - Riza, Ramzul Irham; Riyadi, Tri Widodo Besar; Wijianto, W (Prosiding Simposium Nasional Rekayasa Aplikasi Perancangan dan Industri, 2024)
Ceramics have been attractive as advance materials for high temperature applications due to their advantages such as high modulus, high hardness, high melting temperature, and high corrosion resistance. Of a broad range of ceramics, titanium carbide and aluminide have developed into one of the most interesting ceramics since they have high strength and good wear resistance at elevated ceramic materials. Producing TiC-Al2O3 from economical material (TiO2) is less expensive than that from their elemental powders. The combustion synthesis (CS) process offers significant advantages to fabricate TiC-Al2O3 since it produces high exothermic reaction and takes a short processing time. The objective of this study was to explore the combustion synthesis of TiC-Al2O3 and investigate the effect of reactant compositions on the combustion process and microstructure of synthesized products. The combustion synthesis was carried out in a combustion chamber with an atmospheric condition. The ignition technique to initiate the CS was performed using an arc flame. The microstructure and mechanical properties of synthesized products were observed. The result of this research would benefit for producing a high performance ceramic material obtained from economical material with an efficient process.